Dynamic Governance and The Strengthening Community Participation in Countermeasure Coronavirus Disease - Ahmad Sururi; Rostiena Pasciana (Iapa Proceedings Conference, 2020)
This article discusses the strengthening public participation in the countermeasure and prevention of coronavirus disease-19. The main issue in this study is related to the complexity of the problem to counteract and prevent Covid-19, such as the existence of a gap between planning and objectives in government policy instruments, lack of public participation, and awareness in supporting government policies in preventing Covid-19. Preliminary observations made by researchers indicate the importance of examining research issues using dynamic governance theory and policy instruments. The research was conducted using a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation study. The preliminary findings of the study indicate that the implementation of dynamic governance capacity, and public participation in the countermeasure and prevention of Covid-19 has not been fully implemented due to several factors, such as the inadequate capabilities of public sector organizations, internalization of government organizational culture and problems of community participation. Therefore, it is necessary to encourage strategic policy instruments through the dynamic governance concept approach to support the success of the countermeasure and prevention of Covid-19.